Short‐ versus Long‐term Stenting in Children with Subglottic Stenosis Undergoing Laryngotracheal Reconstruction. (24th October 2017) - Smith, David F.; de Alarcon, Alessandro; Jefferson, Niall D.; Tabangin, Meredith E.; Rutter, Michael J.; Cotton, Robin T.; Hart, Catherine K.
Abstract : Objectives: Suprastomal stents are routinely used in laryngotracheal reconstruction (LTR) to stabilize grafts and provide framework to sites of repair. However, the duration of stenting varies according to patient history and physician preference. We examined outcomes of short‐ versus long‐term stenting in children with subglottic stenosis (SGS) undergoing LTR. Study Design: Case series with chart review. Setting: Tertiary care pediatric hospital. Subjects and Methods: Thirty‐six children <18 years old who underwent double‐stage LTR for SGS from January 2012 to January 2015 were included. Demographic data, stenosis grade, and decannulation rates were compared between children with short‐term stenting (≤21 days; n = 14) and those with long‐term stenting (>21 days; n = 22). Results: No significant difference between groups was seen for sex, age, race, or previous repair. Children in the short‐term group were stented for 10.9 ± 4.9 days, compared with 44.0 ± 10.6 for those long‐term ( P <. 0001). A similar number of children with short‐ versus long‐term stents had grade 3/4 stenosis preoperatively (71.4% vs 77.2%). Although time to decannulation was not significantly different, 72.7% of children with long‐term stents were decannulated, as opposed to 35.7% with short‐term stents ( P =. 03). After adjusting for grade at surgery and age, children with long‐term stents had 4.3 greater odds (95% CI, 1.0‐18.3) of decannulation than children with short‐term stents. Conclusions: Children with long‐term stenting were more likely to be successfully decannulated. Although long‐term stenting improved outcomes for children with SGS, additional research is needed to better define ideal candidates for short‐ versus long‐term stenting.